2004
DOI: 10.1111/j.1420-9101.2003.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing alternative models for sexual isolation in natural populations of Littorina saxatilis: indirect support for by-product ecological speciation?

Abstract: Two ecotypes of the rough periwinkle Littorina saxatilis occur at different shore levels, showing assortative mating for size and partial reproductive isolation when they meet at the mid‐shore. This system represents a putative case of incomplete speciation in sympatry. Two processes contribute to the assortative mating: morph‐specific microhabitat aggregation and mate choice. The estimation of mate choice coefficients in nature and a simulation of the aggregation effects on sexual isolation were used to disen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 40 publications
6
98
0
Order By: Relevance
“…Such ecotype differences that are strongly correlated to different habitat type along the shore were extensively studied in Littorina saxatilis (see for critical review Butlin et al 2008). In this marine gastropod, repeated experimental work has demonstrated that strong divergent natural selection acting across an environmental gradient is the mechanism that maintains ecotypic divergence in spite of ongoing gene flow (Rolán-Alvarez et al 1997, Cruz et al 2004a. However, demonstrating speciation with gene flow is far from easy due to the difficulty of separating the effects of time since divergence from gene flow (but see review of Nosil 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Such ecotype differences that are strongly correlated to different habitat type along the shore were extensively studied in Littorina saxatilis (see for critical review Butlin et al 2008). In this marine gastropod, repeated experimental work has demonstrated that strong divergent natural selection acting across an environmental gradient is the mechanism that maintains ecotypic divergence in spite of ongoing gene flow (Rolán-Alvarez et al 1997, Cruz et al 2004a. However, demonstrating speciation with gene flow is far from easy due to the difficulty of separating the effects of time since divergence from gene flow (but see review of Nosil 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, the by-product mechanism is still implicated when differentially adapted populations produce fully functional hybrids, as there is then no incentive to avoid hybridization. For example, hybrids between the lower and upper shore morphs of the marine snail Littorina saxatilis are fitter than either parent in the midtidal zone, yet there is still some assortative mating between the parental morphs (Rolan-Alvarez et al 1997;Cruz et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…That is, snails crossing habitat borders (either by creeping or by rafting) reduce their chance of survival to about 10 -20% of their earlier value ( Janson 1983;Rolán-Alvarez et al 1997). In addition, parental ecotype snails disperse non-randomly at least in the Spanish hybrid zone, contributing to the gene flow barrier Cruz et al 2004). The presence of a postzygotic component of isolation has been suggested from observations from a hybrid zone in the UK, where five hybrid females out of seven sampled had strongly elevated levels of aborting embryos (Hull et al 1996).…”
Section: Evidences Of Partial Reproductive Isolationmentioning
confidence: 99%